The Nature of Lexical-Semantic Access in Bilingual Aphasia. (30th March 2014) - Kiran, Swathi; Balachandran, Isabel; Lucas, Jason
Abstract : Background. Despite a growing clinical need, there are no clear guidelines on assessment of lexical access in the two languages in individuals with bilingual aphasia. Objective. In this study, we examined the influence of language proficiency on three tasks requiring lexical access in English and Spanish bilingual normal controls and in bilingual individuals with aphasia. Methods. 12 neurologically healthy Spanish-English bilinguals and 10 Spanish-English bilinguals with aphasia participated in the study. All participants completed three lexical retrieval tasks: two picture-naming tasks (BNT, BPNT) and a category generation (CG) task. Results. This study found that across all tasks, the greatest predictors for performance were the effect of group and language ability rating (LAR). Bilingual controls had a greater score or produced more correct responses than participants with bilingual aphasia across all tasks. The results of our study also indicate that normal controls and bilinguals with aphasia make similar types of errors in both English and Spanish and develop similar clustering strategies despite significant performance differences between the groups. Conclusions. Differences between bilingual patients and controls demonstrate a fundamental lexical retrieval deficit in bilingual individuals with aphasia, but one that is further influenced by language proficiency in the two languages.